Cultural adaptations and cultural factors in EBI implementation with Latinx communities - Castro, Felipe González; Berkel, Cady; Epstein, Dana R. (Frontiers in Public Health, 2023)
Introduction Cultural factors are constructs that capture important life experiences of Latinx/Hispanic individuals, families, and communities. Despite their importance for Latinx communities, Latinx cultural factors have yet to be fully incorporated into the literature of many social, behavioral science, and health service fields, including implementation science. This significant gap in the literature has limited in-depth assessments and a more complete understanding of the cultural life experiences of diverse Latinx community residents. This gap has also stifled the cultural adaptation, dissemination, and implementation of evidence based interventions (EBIs). Addressing this gap can inform the design, dissemination, adoption, implementation, and sustainability of EBIs developed to serve Latinx and other ethnocultural groups. Methods Based on a prior Framework Synthesis systematic review of Latinx stress-coping research for the years 2000–2020, our research team conducted a thematic analysis to identify salient Latinx cultural factors in this research field. This thematic analysis examined the Discussion sections of 60 quality empirical journal articles previously included into this prior Framework Synthesis literature review. In Part 1, our team conducted an exploratory analysis of potential Latinx cultural factors mentioned in these Discussion sections. In Part 2 we conducted a confirmatory analysis using NVivo 12 for a rigorous confirmatory thematic analysis. Results This procedure identified 13 salient Latinx cultural factors mentioned frequently in quality empirical research within the field of Latinx stress-coping research during the years 2000–2020. Discussion We defined and examined how these salient Latinx cultural factors can be incorporated into intervention implementation strategies and can be expanded to facilitate EBI implementation within diverse Latinx community settings.